Upcycling C&D Waste via Mechanical Abrasion: Balancing Aggregate Quality Enhancement against Process-Induced Damage - Kanaujia, Subhas Chandra; Ahmad, Syed Aqeel; Khan, Zishan Raza; Singh, Vikash (Three E Science Institute, 2025)
The construction industry is a significant consumer of natural aggregates and a major contributor to carbon emissions. Recycled Concrete Aggregates (RCA) derived from Construction and Demolition (C&D) waste offer a promising sustainable alternative. This study examines how mechanical abrasion affects RCA processed in a Los Angeles (LA) abrasion drum with revolutions ranging from 100 to 1000 to find an optimal treatment window that maximizes quality without causing aggregate damage. The results indicate that coarse RCA processed at 500–600 revolutions significantly improved specific gravity ( 2.55 from 2.3) and reduced water absorption ( 2.0% from 4-5%), meeting the standards for natural aggregates. This treatment effectively removed fine mortar particles and improved durability (soundness loss 15%), surpassing untreated RCA, which exhibited soundness losses >30%. However, excessive abrasion beyond 700 revolutions led to an increase in fines and micro-cracking, resulting in a soundness loss exceeding 23%, failing durability criteria. The optimal abrasion range ( 500 revolutions) resulted in a coarse aggregate yield of about 50%, compared to only 27% at 1000 revolutions. The study shows that on-site processing of C&D waste at this optimal level produces high-value aggregates for structural concrete, supporting the circular economy by reducing dependence on virgin aggregates and diverting waste from landfills. Cost analysis indicates that moderate abrasion ( 500 revolutions) maximizes net material value while minimizing energy use and dust production. These results emphasize the viability of mechanical abrasion as a sustainable upcycling method for RCA, balancing quality improvement with process-related damage.